2014
DOI: 10.1289/ehp.1307918
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral Function in School-Age Children Exposed to Manganese in Drinking Water

Abstract: Background: Manganese neurotoxicity is well documented in individuals occupationally exposed to airborne particulates, but few data are available on risks from drinking-water exposure.Objective: We examined associations of exposure from concentrations of manganese in water and hair with memory, attention, motor function, and parent- and teacher-reported hyperactive behaviors.Methods: We recruited 375 children and measured manganese in home tap water (MnW) and hair (MnH). We estimated manganese intake from wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
153
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(164 citation statements)
references
References 35 publications
6
153
1
4
Order By: Relevance
“…Other cross-sectional epidemiologic studies have also observed sex-specific differences in associations between Mn levels measured in childhood and neurological outcomes (Bouchard et al 2011; Lucchini et al 2012a; Menezes-Filho et al 2014; Riojas-Rodriguez et al 2010; Torres-Agustín et al 2013), while some have not (Bouchard et al 2007; Chung et al 2015; Hernández-Bonilla et al 2011; Lucchini et al 2012b; Oulhote et al 2014a; Riojas-Rodriguez et al 2010). In 7–12 year-old girls living near Mn mining or ferro-manganese industry, hair Mn concentrations were negatively associated with scores on the Wechsler Intelligence Scale for Children (n=172) (Riojas-Rodríguez et al 2010), verbal learning and memory (Torres-Agustín et al 2013), and inattention and externalizing behavior (n=70)(Menezes-Filho et al 2014).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Other cross-sectional epidemiologic studies have also observed sex-specific differences in associations between Mn levels measured in childhood and neurological outcomes (Bouchard et al 2011; Lucchini et al 2012a; Menezes-Filho et al 2014; Riojas-Rodriguez et al 2010; Torres-Agustín et al 2013), while some have not (Bouchard et al 2007; Chung et al 2015; Hernández-Bonilla et al 2011; Lucchini et al 2012b; Oulhote et al 2014a; Riojas-Rodriguez et al 2010). In 7–12 year-old girls living near Mn mining or ferro-manganese industry, hair Mn concentrations were negatively associated with scores on the Wechsler Intelligence Scale for Children (n=172) (Riojas-Rodríguez et al 2010), verbal learning and memory (Torres-Agustín et al 2013), and inattention and externalizing behavior (n=70)(Menezes-Filho et al 2014).…”
Section: Discussionmentioning
confidence: 94%
“…With one exception (Mora et al 2015), most epidemiologic studies that assessed childhood Mn exposure and learning and memory were cross-sectional in design and contained no prenatal or postnatal Mn measurements (Haynes et al 2015; Hernández-Bonilla et al 2016; Nascimento et al 2016; Oulhote et al 2014a; Torres-Agustín et al 2013; Wasserman et al 2011; Wright et al 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Oulhote et al (2014) reported a significant linear association between intake of Mn in drinking water and poorer motor function index, derived by a latent variable representing hand dexterity and coordination, in 6–13 year-old children in Canada (Oulhote et al, 2014a). Hernández-Bonilla et al found suggestive associations between higher blood Mn with poorer motor speed and coordination in children aged 7–11 years in Mexico, although not for hair Mn (Hernández-Bonilla et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Mn is present ubiquitously in grains, green vegetables, fruits, nuts, spices, and tea and cases of Mn deficiency are uncommon (Roth, 2006). The presence of excessive Mn levels in drinking water or air has been associated with poorer memory and attention (Carvalho et al, 2014;Oulhote et al, 2014) and hyperactive behavior (Bouchard, 2007) in school-aged children. Water containing elevated Mn levels also had adverse effects on 10-year-old children's cognitive function (Wasserman et al, 2006).…”
mentioning
confidence: 99%